Customer trust moderates content marketing and customer rating effect on e-commerce purchase intention - Harman Malau; Deske W Mandagi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
The rapid growth of e-commerce in Indonesia has intensified competition among online platforms to attract consumers' purchase intentions. In this highly competitive digital environment, content marketing and customer ratings have become important determinants of purchase intention. However, the effectiveness of these factors may depend on the level of customer trust in e-commerce platforms. This study aims to examine the effects of content marketing and customer ratings on purchase intention and to investigate the moderating role of customer trust. A quantitative research approach was employed using a survey of university students in Bandung who had previous experience purchasing products through e-commerce platforms. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that both content marketing and customer ratings have positive and significant effects on purchase intention. Furthermore, customer trust significantly strengthens the relationships between content marketing, customer ratings, and purchase intention. These findings indicate that higher consumer trust enhances the effectiveness of digital marketing strategies in encouraging purchase intention. This study contributes to the consumer behavior literature by extending the understanding of customer trust as a moderating variable rather than solely as a direct or mediating factor. Practically, the findings provide valuable insights for e-commerce companies to improve marketing content quality, optimize customer rating systems, and strengthen consumer trust to increase purchase intention.